The Level of Stakeholders/Users Satisfaction (in Tourism Industries) Toward the Graduates of Sekolah Tinggi Pariwisata Mataram - Fathurrahim Fathurrahim (Journal of Economics Research and Social Sciences, 2023)
The target of this research is the alumni/graduates of the Sekolah Tinggi Pariwisata Mataram (STP) who have worked in the field of tourism services (hotels) on the island of Lombok in West Nusa Tenggara. This research is intended to map the level of user satisfaction in terms of aspects (ethics, expertise in the field of science, mastery of technology and information, communication skills, cooperation, self-development, and foreign language skills) alumni/graduates of the STP Mataram Hospitality Study Program on several aspects of ability. This research is focused on the D3 Hospitality program through a survey study of 25 respondents (stakeholders/users) in the tourism service industry (hospitality). Data were collected through observation, filling out questionnaires and documentation studies using descriptive-quantitative analysis. This study found that aspects of integrity, professionalism, understanding of technology, teamwork, and self-development of STP Mataram alumni were at a good level. Meanwhile, their English-speaking ability is still weak. This research is expected to be useful for: (1) increasing the quality of STP Mataram graduates who are moral, ethical, and with integrity according to the tourism culture, (2) strengthening skills, knowledge, and attitudes in the tourism service industry, and (3) strengthening understanding and skills digital tourism (digital tourism) in the millennium era (industry 4.0) with the use of technology which has become a tourism development paradigm. This research is targeted to be carried out for 4 months with the personnel involved, namely three research lecturers.